2013
DOI: 10.7717/peerj.102
|View full text |Cite
|
Sign up to set email alerts
|

Affect-focused psychodynamic psychotherapy for depression and anxiety through the Internet: a randomized controlled trial

Abstract: Background. Psychodynamic psychotherapy is a psychological treatment approach that has a growing empirical base. Research has indicated an association between therapist-facilitated affective experience and outcome in psychodynamic therapy. Affect-phobia therapy (APT), as outlined by McCullough et al., is a psychodynamic treatment that emphasizes a strong focus on expression and experience of affect. This model has neither been evaluated for depression nor anxiety disorders in a randomized controlled trial. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
101
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 47 publications
1
101
2
1
Order By: Relevance
“…The affect-focused treatment used could be placed in a class of psychodynamic treatments called Experiential Dynamic Therapies (Osimo & Stein, 2012). The present article complements the recently published Johansson et al (2013) controlled trial with a detailed description of the treatment, practical examples, and case excerpts.…”
Section: Psychodynamic Guided Self-help Through the Internetmentioning
confidence: 99%
See 3 more Smart Citations
“…The affect-focused treatment used could be placed in a class of psychodynamic treatments called Experiential Dynamic Therapies (Osimo & Stein, 2012). The present article complements the recently published Johansson et al (2013) controlled trial with a detailed description of the treatment, practical examples, and case excerpts.…”
Section: Psychodynamic Guided Self-help Through the Internetmentioning
confidence: 99%
“…These two studies were the first to provide evidence that psychodynamic psychotherapy delivered through the Internet could be effective. Third, the most recent development, was a treatment study in which an affect-focused, psychodynamic intervention was tested on mixed groups of people with depression and anxiety disorders (Johansson et al, 2013). In that study, the treatment was shown to have a large effect on depression and a moderately large effect on anxiety, when compared to a control group who received nonspecific online support.…”
Section: Psychodynamic Guided Self-help Through the Internetmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though ICBT is the most studied method, there are also studies showing that other orientations such as psychodynamic (Johansson, Björklund, Hornborg, Karlsson, Hesser, Ljótsson, et al, 2013a) and interpersonal therapy (Donker et al, 2013) can be effective internet-based treatment methods for treating depression.…”
Section: Internet-based Cbt For Depressionmentioning
confidence: 99%